Developing Practical Approaches to Active Preservation - Adrian Brown (International Journal of Digital Curation, 2008)
The National Archives is developing a range of practical solutions to the active preservation of electronic records, using an extensible service-oriented architecture and a central technical registry (PRONOM). This paper describes TNA’s methodologies for characterisation, preservation planning, and preservation action, the technologies being adopted to implement them, and the role of PRONOM in supporting these services. It describes how this approach fits with international research programmes, and the types of preservation service which TNA may be able to provide externally in the future.